Amanat Tok Guru Tok Guru jawab pelawaan Dr. Mahathir - Abdul Aziz bin Nik Mat, Haji Nik, 1931-2015. (KL. [i.e. Kuala Lumpur] : Diterbit edar oleh Perniagaan Al-Baiyyinah, 1996)
Politics and government, Islam and politics in Malaysia; speeches by leaders of PAS, Parti Islam Semalaysia, the Islamic Party of Malaysia.
Title from container insert.
Production level cataloging.
In Malay.
Keywords: Parti Islam SeMalaysia; Islam and politics -- Malaysia; Speeches, addresses, etc., Malay -- Malaysia; Malaysia -- Politics and government